Access to justice in prisons or the limitations of prison defense - Carvacho, Pablo (Crime, law and social change, 2023)
This article sought to understand the adequacy of criminal defense services within prisons. By analyzing secondary data and interviews, it describes the justiciable problems and legal needs, the lines of action, and the obstacles that the adult prison population encounters. The results show that the experience and needs that arise in prison surpass the institutional capabilities of the chilean Public Defender’s Office. Therefore, a new institutional framework must be created to meet the justice claims of prisoners.